Partisipasi Masyarakat dalam Pengembangan Wisata Halal serta Dampaknya terhadap Perekonomian (Studi Kasus : Kawasan Wisata Religi Makam Gus Dur) - Saniyatul Ayu Aprilia; Sri Abidah Suryaningsih (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The development of Islamic economy in recent decades has not only had an impact on banking and financial sectors, but also has an impact on tourism sector. The tourism sector is second highest sector contributing to the country's foreign exchange. This research is field research with qualitative descriptive that aims to determine community participation in developing halal tourism in religious tourism area of Gus Dur’s Tomb, supporting factors and obstacles to community participation in development of halal tourism, the impact of tourism development on the economy of surrounding community. The data types used are primary and secondary data. The data collection technique to obtain primary data is conducting interviews. Secondary data’s from books, journals, and other literature that’s relevant to the research. The results showed that local communities actively participated in form of energy, property, expertise, crafts, and social. The encourages factor in participating is high awareness to advancing tourism. Main inhibiting factor in participating is lack of accompanying personnel for the community. The impact of tourism development on local community's economy are increase income, create business and employment opportunities.